Preparation of Pb(Zr,Ti)O-3 thin films by soft chemical route - Pontes, F. M.; Leite, E. R.; Nunes, MSJ; Pontes, DSL; Longo, Elson [UNESP]; Magnani, R.; Pizani, P. S.; Varela, José Arana [UNESP] (Elsevier B.V., 2004)
Lead zirconate titanate, Pb(Zr0.3Ti0.7)O-3 (PZT) thin films were prepared with success by the polymeric precursor method. Differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), Fourier-transform infrared spectroscopy (FT-IR), Micro-Raman spectroscopy and X-ray diffraction (XRD) were used to investigate the formation of the PZT perovskite phase. X-ray diffraction revealed that the film showed good crystallinity and no presence of secondary phases was identified. This indicates that the PZT thin films were crystallized in a single phase. PZT thin films showed a well-developed dense grain structure with uniform distribution, without the presence of rosette structure. The Raman spectra undoubtedly revealed these thin films in the tetragonal phase. For the thin films annealed at the 500-700 degreesC range, the vibration modes of the oxygen sublattice of the PZT perovskite phase were confirmed by FT-IR. The room temperature dielectric constant and dielectric loss of the PZT films, measured at 1 kHz were 646 and 0.090, respectively, for thin film with 365 nm thickness annealed at 700 degreesC for 2 h. A typical P-E hysteresis loop was observed and the measured values of P-s, P-r and E-c were 68 muC/cm(2), 44 muC/cm(2) and 123 kV/cm, respectively. The leakage current density was about 4.8 x 10(-7) A/cm(2) at 1.5 V. (C) 2003 Elsevier Ltd. All rights reserved.
Keywords: dielectric properties; films; Pb(Zr,Ti)O-3; PZT